2020
DOI: 10.1111/1440-1703.12190
|View full text |Cite
|
Sign up to set email alerts
|

High variation of mitochondrial DNA diversity as compared to nuclear microsatellites in mammalian populations

Abstract: The effective gene number (the number of genes that can be inherited) of mitochondrial DNA (mtDNA) is one‐fourth of that of nuclear DNA (ncDNA) in idealized populations. Therefore, mtDNA haplotype diversity (h) is predicted to be lower than ncDNA heterozygosity (HE) because of the higher effect of genetic drift on mtDNA. This prediction has not yet been systematically tested. To this end, in this study, published data for 739 populations of 108 mammalian species (66 terrestrial and 42 marine species) revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Wimmer et al (2002) found 13 mtDNA haplotypes in 85 individuals of M. murinus, revealed 4 haplotypes among 46 individuals (sampled in 1 year) of the sympatric Mirza coquereli, and Gerloff et al (1999) detected 5 haplotypes in a population of 36 bonobos. The mtDNA haplotype diversity of M. griseorufus (0.921), calculated according to Saitoh (2021), is higher than that of M. murinus (0.508) and M. coquereli (0.660). While it is difficult to compare different higher taxa, social units, and sampling areas, M. grisoeurufus is very diverse and ranks among the top 15% of the 66 terrestrial mammal species compiled by Saitoh (2021).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Wimmer et al (2002) found 13 mtDNA haplotypes in 85 individuals of M. murinus, revealed 4 haplotypes among 46 individuals (sampled in 1 year) of the sympatric Mirza coquereli, and Gerloff et al (1999) detected 5 haplotypes in a population of 36 bonobos. The mtDNA haplotype diversity of M. griseorufus (0.921), calculated according to Saitoh (2021), is higher than that of M. murinus (0.508) and M. coquereli (0.660). While it is difficult to compare different higher taxa, social units, and sampling areas, M. grisoeurufus is very diverse and ranks among the top 15% of the 66 terrestrial mammal species compiled by Saitoh (2021).…”
Section: Discussionmentioning
confidence: 75%
“…The mtDNA haplotype diversity of M. griseorufus (0.921), calculated according to Saitoh (2021), is higher than that of M. murinus (0.508) and M. coquereli (0.660). While it is difficult to compare different higher taxa, social units, and sampling areas, M. grisoeurufus is very diverse and ranks among the top 15% of the 66 terrestrial mammal species compiled by Saitoh (2021).…”
Section: Discussionmentioning
confidence: 75%
“…Genetic differentiation statistics were also calculated by SNP data (Text S1). Generally, genetic diversity and genetic drift pressure differ between nuclear DNA and mtDNA (Toews and Brelsford 2012;Morin et al 2018;Saitoh 2021). However, at the spatial scale at which gene flow is dominant, because the theoretical pattern of being inversely proportional to migration is common (Allendorf et al 2022), genetic differentiation should be synchronized regardless of markers in the absence of sex differences.…”
Section: Population Structure Genetic Diversity and Genetic Different...mentioning
confidence: 99%
“…Tigers are known to exhibit female philopatry and male-biased dispersal therefore we may expect to see stronger structure in matrilineally inherited markers. This pattern of male-biased dispersal is common among mammals and results in patterns of nested mitochondrial DNA structure even when there is continued gene flow [74,75]. While this pattern of NE divergence reflects the inferences in Kolipakam et al [40], PCA and structure analysis in Armstrong et al [36] do not show this separation, and our genome-wide analysis indicates that the NE does not differentiate until higher K. This outcome and the shared ancestry between the NE and some CI populations in Kolipakam et al [40] suggests that there has been continued gene flow between tigers in the NE and CI.…”
Section: (B) Nuclear Markersmentioning
confidence: 99%